2005
DOI: 10.21273/jashs.130.4.605
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of Mannitol-1-Phosphate Dehydrogenase Increases Mannitol Accumulation and Adds Protection Against Chilling Injury in Petunia

Abstract: Petunia ×hybrida (Hook) Vilm. cv. Mitchell was transformed with an E. coli gene encoding mannitol-1-phosphate dehydrogenase (mtlD). Four plant lines that grew on kanamycin and contained the mtlD transgene were identified. Two of these lines contained high levels of mannitol [high-mannitol lines M3 and M8; mean mannitol = 3.39 μmol·g-1 dry weight (DW… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
19
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 29 publications
3
19
0
Order By: Relevance
“…However, these results also demonstrated that the amount of accumulated mannitol was too small to account for its effect as an osmolyte; therefore, the authors suggested that it might act as an oxygen free radical scavenger. Similar results have been reported for transgenic eggplants (Prabhavathi et al 2002) and petunia (Chiang et al 2005) that expressed the bacterial mtlD gene. Enhanced tolerance to salt stress has also been reported in trees such as loblolly pine (Tang et al 2005) and poplar (Hu et al 2005).…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…However, these results also demonstrated that the amount of accumulated mannitol was too small to account for its effect as an osmolyte; therefore, the authors suggested that it might act as an oxygen free radical scavenger. Similar results have been reported for transgenic eggplants (Prabhavathi et al 2002) and petunia (Chiang et al 2005) that expressed the bacterial mtlD gene. Enhanced tolerance to salt stress has also been reported in trees such as loblolly pine (Tang et al 2005) and poplar (Hu et al 2005).…”
Section: Discussionsupporting
confidence: 85%
“…However, the mannitol content in individual lines was variable. Similar results have been reported for transgenic tobacco (Tarczynski et al 1993;Ruperez and Toledano 2003), Arabidopsis (Thomas et al 1995;Zhifang and Loescher 2003), petunia (Chiang et al 2005), loblolly pine (Tang et al 2005), and eggplant (Prabhavathi and Rajam 2007). Variations in the mannitol content may be due to copy number and to the positional effects of the transgene that may result in differential expression of the transgene in different lines (Hobbs et al 1990;Celebi-Toprak et al 2005;Tang et al 2005;Waditee et al 2007).…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…The expression of a bacterial mtlD in Saccharomyces cerevisiae was sufficient to generate mannitol which was proposed to act as an osmolyte and was sufficient to rescue the phenotypes of a glycerol deficient mutant, producing an increased resistance to high salt and H 2 O 2 [45]. Mtl is also proposed to function as an osmoprotectant in cells of petunia as well as improving cold tolerance [46].…”
Section: Discussionmentioning
confidence: 99%
“…An additional gene ectD coding for ectoine hydroxylase (EC: 1/14/11) is present, and this enzyme converts ectoine to hydroxyectoine (15). Furthermore, the genome encoded other osmoprotectant-related enzymes such as trehalose phosphatase (EC:3.1.3.12) (16) and mannitol-1-phosphate 5-dehydrogenase (EC:1.1.1.17) (17), suggesting a possible role for this endophyte in enhancing salinity tolerance in plants.…”
Section: Genome Announcementmentioning
confidence: 99%